Analisis Faktor-Faktor Yang Mempengaruhi Persepsi Pengusaha Kecil Dan Menengah Atas Penggunaan Informasi Akuntansi (Studi Kasus pada Pengusaha Kecil dan Menengah yang Bergerak dibidang Jenis Usaha Makanan di Kecamatan Kemiling) - Jhon Piranda; Kusnadi Kusnadi; Hardini Ariningrum (Universitas Malahayati, 2015)
Abstract, Lack of ability in using accounting information is one of the factors that led to the failure of smalland medium enterprises to develop their business. The purpose of this study was to analyze the influence ofowner education, training of accounting, accounting knowledge and experience in accounting information to theperception of small and medium enterprises on the use of accounting information. This study is expected toprovide empirical evidence on the use of accounting information in small and medium enterprises in Kemiling.The population in this study was in small and medium enterprises in Kemiling. The sampling method usingsimple random sampling (random) amount to 50 small and medium business owners in Kemiling. Data werecollected by distributing a questionnaire to the managers / owners of small and medium-sized businesses inKemiling. These data prior to analysis have been tested for validity and reliability. Data analysis techniquesusing multiple linear regression analysis. The results indicate that the variable partial accounting training (X2),knowledge of accounting (X3) and experience in accounting information (X4) affect the perception of small andmedium entrepreneurs on the use of accounting information (Y). Owner education variable (X,) does not affectthe perception of small and medium entrepreneurs on the use of accounting information (Y). Taken together theindependent variable (X) effect on the dependent variable (Y). Retrieved Adjusted R Square of 0.866 is 86.6%,which means that the dependent variable (Y) is explained by the independent variable (X) and the remaining13.4% is explained by other variables not examined in this study.